Research on Comprehensive Evaluation Method of High Reliability Wiring Mode for Medium Voltage Distribution Network - Jun HAN; Zhenjian XIE; Lu GENG; Hua QIN; Xi CHEN; Na WANG (Zhongguo dianli)
In order to solve the problem that there are too many evaluation indicators and no unified standards for planning and design of medium-voltage distribution network wiring mode in high-reliability area, this paper studies the comprehensive evaluation method of high-reliability wiring mode for medium-voltage distribution network. Firstly, a comprehensive evaluation indicator system of high-reliability wiring mode is constructed from four aspects: reliability, economy, technology and adaptability. Secondly, the DEATEL-ANP-anti-entropy weight method and improved gray correlation method are used to determine the weights of each evaluation indicator. And then, the polynomial difference method is used to analyze the indicator rating function of high-reliability wiring mode. Finally, based on a high-reliability renovation project in a type A area in Jiangsu, a comprehensive evaluation and comparative study is carried out on the single-ring network wiring, double-ring network wiring, petal type wiring and three-way for same supply wiring mode with flexible DC loop. The results show that the three-way for same supply wiring mode with flexible DC loop has higher reliability and applicability with high comprehensive ratings, which conforms to the engineering reality, and proves the feasibility and effectiveness of the proposed comprehensive evaluation method.